Wittgenstein - Phillips, D. Z. author. aut Link
VII, 205 p.
Keywords: According to Wittgenstein, philosophical puzzles are due to deep prejudices about language. In this collection of essays, in honour of Rush Rhees, philosophers investigate the hold such prejudices have on us in a number of closely related areas of philosophical enquiry.